The Samekulturen exhibition - a social actor at the Tromsø University Museum: knowledge production and shifting circumstances - Fonneland, Trude A. (Nordisk Museologi, 2020)
In 1973, the exhibition entitled Samekulturen (The Sámi Culture) opened its doors to the public for the first time, and for over forty years this exhibition has served as an important arena for the dissemination of Sámi culture to tourists, students and other visitors. Exhibitions have social and political consequences. Samekulturen as a social actor that contributes to the production of knowledge is the point of departure for this paper. In the view of the museological and ethno-political contexts in which Samekulturen was produced, the exhibition will be analysed as a historical document revealing how museological practices related to the representation of the Sámi have evolved over time.